(untitled) (Research, Society and Development, 2023)
Objective: to analyze the performance of Family Health teams (eSF) in indicators of chronic diseases in Primary Health Care (PHC) in a municipality in the Brazilian Northeast. Method: ecological study carried out with secondary data from the Health Information System for Primary Care (SISAB), eSUS-APS (PEC) and the Situation Room of the Municipal Health Department of São Cristóvão, Sergipe. 24 eSF were evaluated in August/2022, considering the results of April/2022 in the Situation Room and monitoring module of health conditions of the PEC. Regarding SISAB, Previne Brasil indicators VI and VII in Q1 2022 were considered. Results: the eSF informed the follow-up of 3.625 hypertensive and 1.503 diabetic patients in the Situation Room, among which there were 2.790 (76.97%) and 1.211 (80.58%) citizens with such conditions active in the PEC, respectively. At the federal level, the municipal performance in indicator VI was 19% (numerator of 3.394 and estimated denominator of 18.081) and in VII, 13% (numerator of 757 and identified denominator of 5.764). However, applying the same calculation method with the SISAB numerator and the Situation Room denominator, the municipal performance would be 89% (VI) and 44% (VII). Conclusions: The number of hypertensive and diabetic patients being monitored in the municipal PHC was clearly below the territory’s population estimates, with the need for an active search and strengthening of Care Lines. However, among the hypertensive patients monitored, there was a satisfactory performance in the Situation Room indicators, suggesting a review of the Previne Brasil calculation method, regarding the exclusion of self-reported individuals in these denominators.